A method for extending planar axis-symmetric parallel manipulators to spatial mechanisms. (January 2015) - Isaksson, Mats; Eriksson, Anders; Watson, Matthew; Brogårdh, Torgny; Nahavandi, Saeid
Abstract: This paper investigates axis-symmetric parallel manipulators, composed of a central base column and an arm system able to rotate around this column. The arm system includes several actuated upper arms, each connected to a manipulated platform by one or more lower arm linkages. Such manipulators feature an extensive positional workspace in relation to the manipulator footprint and equal manipulator properties in all radial half-planes defined by the common rotation-axis of the upper arms. The similarities between planar manipulators exclusively employing 2-degrees-of-freedom (2-DOF) lower arm linkages and lower mobility spatial manipulators only utilising 5-DOF lower arm linkages are analysed. The 2-DOF linkages are composed of a link with a 1-DOF hinge on both ends whilst the 5-DOF linkages utilise 3-DOF spherical joints and 2-DOF universal joints. By employing a proposed linkage substitution scheme, it is shown how a wide range of spatial axis-symmetric parallel manipulators can be derived from a limited range of planar manipulators of the same type. Highlights: Axis-symmetric parallel manipulators provide several advantages. A methodology to derive axis-symmetric parallel manipulators is introduced. The core assumption of the proposed methodology is proved using screw theory. Several novel axis-symmetric parallel manipulators are proposed.